Development of turbocharging system for diesel engines of power generation application at different altitudes. Issue 4 (November 2016) - Li, Hualei; Shi, Lei; Deng, Kangyao
Abstract: The environmental atmospheric density reduces with the increased altitude. For turbocharged diesel engines, boost pressure and mass flow rate of fresh air are decreased with the limited plateau self-compensation ability when the altitude increases to a certain value. The decreased air flow results in the reduction of output power of diesel engines, and the diesel engine performances affect the electric power of diesel generator set. Therefore, to solve the problem of diesel generator set operating at plateau, power recovery of diesel engines is essential for maintaining its performance. Boost pressure recovery provides an alternative solution to this problem. In this paper, a turbocharging system was developed for recovering the boost pressure according to a matching process. A control strategy of the waste-gate valve was confirmed, and two operating modes were determined based on the bypass flow ratio. The results show that boost pressure of the engine can be recovered with the matched turbocharging system at different altitudes. However, boost pressure recovery cannot make sure the power recovery of diesel engines due to the changing overall system efficiency and pumping process. Therefore, a method of fuel compensation was proposed, and it can achieve the power recovery target along with the valve control strategy for boost pressure recovery. Highlights: A matching process is presented to recover boost pressure at different altitudes. A valve control strategy is determined based on bypass flow ratio. A method of fuel compensation is proposed to achieve the power recovery target.